(untitled) (New York, 1994)
Details current knowledge of the mechanisms of plant growth and productivity and describes state-of-the-art techniques to isolate, characterize, and manipulate specific plant genes in order to enhance plant productivity. DLC: Crops - Growth.
Keywords: Crops,Crops,Growth (Plants),Plant genetic engineering.,Sự phát triển cây trồng; Growth,Genetic engineering